BAKSO OF SEEDS LAMTORO (LEUCAENA LEUCOCEPHALA) WITH ADDING EGG WHITE AND OLD BOILING (The addition of egg whites and long boiling on the quality of the seed meatballs lamtoro) - Budi Suarti; Umar Ramadhan Batu Bara; Misril Fuadi (AGRIUM: Jurnal Ilmu Pertanian, 2016)
This study aims to know how do make the addition of egg whites and long boiling on the quality of the seed meatballs lamtoro. This study using completely randomized design ( RAL) with two factors. The first factors is addition of egg whites (P), which consists of 4 levels, namely: (P1=10% , P2 = 15%, P3 = 20%, and P4 = 25%). The second Factors is long boiling (L) which consists of 4 levels, namely : (L1 = 10 minute, L2 = 15 minute, L3 = 20 minute, and L4 = 25 minute). Parameters analyzed were protein content, carbohydrate content, tannins content, and organoleptic values of texture, aroma ,and taste.The research result to addition of egg whites gives highly significant effect to protein content, ,organoleptic texture, aroma, and taste, while no significant effect on carbohydrate content, andtannins content. while the long boiling gives highly significant effect on organoleptic texture content, aroma content, and taste content while no significant effect on protein content,carbohydrate content, and tannins content.The interaction between addition of egg whites and long boiling gives no significant effect on protein content, carbohydrate content, tannins content, and organoleptic values of texture, aroma ,and taste. The best comparison treatment in increasing the number of addition of egg whites is 25% and long boiling that is 10 minute.this is because the process of making meatballs from the seeds of this lamtoro give texture, aroma and taste good.Keywords: egg whites, lamtoro seeds, water, tapioka flour, wheat flour, meatballs